The development, implementation, and evaluation of an individualized self-assessment process for life-long learning - Hunder, Carrol D. (My University, 2017)
This Capstone graduate project details the development of an individualized self-assessment process for life-long learning, its implementation, and evaluation. The goal was to enable the author to identify and engage in areas for self-growth at the time of the project development, and potentially prepare that process for use by others. The process included an exploration of literature relative to life-long learning; discovery of an appropriate self-assessment instrument that would assess learning dimensions; development of a model to provide a visual presentation of prioritized self-growth areas; and development of activities to strengthen self-growth areas along with outputs and potential outcomes for those activities. It was the intent of the author to document the entire process in order to move forward in the author's personal life-long learning journey, as well as to prepare this process for potential use by others in their life-long learning journeys. The discoveries along the way in this process are documented in the conclusions and recommendations, as well as through the self-reflections of the author
Keywords: Self-evaluation; Continuing education